Grain structure control of titanium alloys during wire + arc additive manufacturing - Wainwright, James Christopher Julian (Cranfield University, 2023)
Prior-β grain structure control of titanium alloys during Wire + Arc Additive Manufacturing (WAAM) is reliant on post-processing following deposition. Multiple methods are typically employed including cold working, melt pool agitation, inoculation and constitutional additions, all of which have distinct limitations. This research has demonstrated prior-β grain structure control in the as-deposited condition whilst utilising a stable deposition process. Prior-β grain structure control of Ti-6Al-4V was achieved through the reduction of the specific energy density of deposited material (SED). As SED decreased, the thermal gradient and potential for constitutional supercooling increased. A linear thermal gradient approximation was calculated via pyrometry to record the melt pool temperature. The SED was controlled via the wire feed speed and fixed energy input. It was determined that SED did not affect the peak melt pool temperature. Instead, arc shading was responsible for the cooling of the melt pool. Electron back-scattered diffraction (EBSD) analysis demonstrated a refinement of the prior-β grain morphology and weakening of texture. Analysis of the prior-β grain boundary misorientations demonstrated that as SED reduced, the misorientations had a propensity to the Mackenzie distribution. However, distinct peaks of 51° <110>β and 60° <111>β misorientations were observed and the tilting of grains to the deposition direction. The SED hypothesis was tested using various process parameters and additional titanium alloys, Ti-6Al-2Sn-4Zr 2Mo and Ti-5Al-5Mo-5V-3Cr, which had an increased potential for constitutional supercooling. It was determined that SED was not the primary mechanism behind prior β grain refinement. Instead, dendrite twinning in the {332}β <113>β and {112}β <111>β during solidification characterised by 51° <110>β and 60° <111>β misorientations respectively, as melt pool curvature, measured by the length/depth ratio proxy, increased. The single energy source deposition was limited by the reliance of melt pool shape on the SED. Therefore, the applicability of a scanning laser and arc multi energy source (MES) system was investigated for the deposition of Ti-6Al-4V. It was demonstrated via optical microscopy that the bead width, height and melt pool length could be independently controlled from the SED. Using the MES system various melt pool length/depth ratios were deposited whilst maintaining an equivalent SED. This confirmed the melt pool shape as controlling factor of the prior-β grain structure morphology via EBSD analysis.
Ding, Jialuo - Associate Supervisor
Keywords: Plasma arc welding; direct energy deposition; columnar-to-equiaxed transition; laser welding; hybrid additive manufacturing; melt pool shape control; dendrite twinning; specific energy density